ELECTRIC AND MAGNETIC PROPERTIES OF Ni0.475Zn0.475Li0.025Al0.025Fe2O4 DOPED (Bi0.5Na0.5)0.94Ba0.06TiO3 CERAMICS PREPARED BY THE SOLID-STATE COMBUSTION METHOD - Pattanakasem, Wiwat; Sookboon, Chirarat; Somsri, Widchaya; Vittayakorn, Naratip; Pinitsoontorn, Supree; Rittidech, Aurawan; Jantaratana, Pongsakorn; Udeye, Thanya; Bongkarn, Theerachai (My University, 2025)
In this study, we synthesized (1-x)((Bi0.5Na0.5)0.94Ba0.06TiO3)-x Ni0.475Zn0.475Li0.025Al0.025Fe2O4 [(1-x)BNBT-xNZLAF] ceramics with x= 0, 0.05, 0.10, 0.15, and 0.20 using the solid-state combustion method. The phase formation, microstructure, and dielectric, ferroelectric, ferromagnetic, and magnetoelectric properties were investigated. BNBT and NZLAF powders were calcined at 750°C and 900°C for 2 h., respectively. The calcined powders were then mixed in various ratios to produce (1-x)BNBT-xNZLAF composites, which were sintered at 1125°C for 2 h. X-ray diffraction analysis indicated that undoped BNBT ceramics exhibited a typical perovskite structure with coexisting rhombohedral (R) and tetragonal (T) phases. With increasing NZLAF content, the cubic spinel (C) phase emerged with the R and T perovskite phases. Rietveld refinement indicated a higher percentage of the C phase as x increased. When x increased from 0 to 0.10, the average grain size and density increased (from 1.0 to 9.8 m and 5.45 to 5.61 g/cm3, respectively) followed by a drop at higher NZLAF levels. Doping BNBT ceramics with NZLAF resulted in a reduction in the dielectric constant (εr), dielectric loss (tan δ), and remnant polarization (Pr). The undoped BNBT ceramic showed a saturated P-E hysteresis loop, while NZLAF doped ceramics exhibited unsaturated P-E loops and increased leakage current. Magnetic measurements showed a transition from diamagnetic to ferromagnetic behavior with NZLAF doping. As x increased, the remnant magnetization (Mr), saturation magnetization (Ms), and magnetoelectric coefficient also increased (Mr0.058 emu/g, Ms3.594 emu/g, and MEcoefficient 2.64 mV/cm•Oe at x=0.25). These results suggest that NZLAF-doped BNBT ceramics hold potential for multiferroic material applications.
Keywords: BNBT; Combustion Method; Dielectric; Microstructure; Multiferroic; NZLAF